2005
DOI: 10.1536/ihj.46.477
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Positive Cases for B-type Natriuretic Peptide and ECG Testing for Identification of Precursor Forms of Heart Failure in an Elderly Population

Abstract: SUMMARYPlasma B-type natriuretic peptide (BNP) levels have been reported to be elevated in various types of cardiac disorders and in precursors of CHF. To elucidate the potential ability of BNP testing to identify individuals with structural cardiac disease (ie, hypertensive heart disease, coronary heart disease, valvular heart disease) among communitydwelling elderly persons, cases which were positive on BNP testing were compared to those positive on ECG testing.In the initial phase, we performed plasma BNP m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Plasma BNP assays were performed for 65.6% of the subjects in the study. The method for measuring plasma BNP levels was previously described in detail [8].…”
Section: Biochemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma BNP assays were performed for 65.6% of the subjects in the study. The method for measuring plasma BNP levels was previously described in detail [8].…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…Both mean hsCRP level in all subjects and that in subjects after excluding subjects with hsCRP levels greater than 10 mg/L are shown in this study. We defined high BNP level as 50 pg/mL or more according to our previous study [8]. Macroalbuminuria was defined as UACR being 300 mg/g or more, and microalbuminuria was defined as UACR being 30 mg/g or more and less than 300 mg/g.…”
Section: Classification and Definitionmentioning
confidence: 99%
“…Furthermore, the prognostic role of the BNP/NT-proBNP assay was well demonstrated in primary care HF patients (17,71). Finally, compared to standard echocardiography, the BNP/ NT-proBNP assay shows lower cost and similar diagnostic accuracy (87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101), and peptide measurement may be preferred, due to its better efficiency, in screening of high-risk populations, such as elderly patients (99)(100)(101), or for assessment of diastolic dysfunction (2,104,105). Collaboration between generalists and cardiologists, rather than solo care by either, which is associated with better HF processes and outcomes of care (106), would benefit from the correct application of natriuretic peptide testing in primary care.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have revealed relationships between BNP and age, BNP and lipids, and BNP and gender as well as the usefulness of BNP in predicting the risk and severity of ischemic heart disease and arrhythmia [8][9][10][11][12]. A few studies have also shown the sensitivity and specificity of BNP in predicting the risk of heart disease in comparison to electrocardiographic (ECG) and echocardiographic findings, but as these have all been one-time measurements of BNP, the significance of the findings is still under debate [13][14][15][16][17][18][19]. Long-term changes in BNP with respect to metabolic syndrome factors have also been investigated [20], but a relationship to changes in ECG findings has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%